DIAGNOSTICS AND TREATMENT OF TONSILLITIS IN CHILDREN FROM THE STAND OF EVIDENCE-BASED MEDICINE - T.V. Spichak ("Paediatrician" Publishers LLC, 2010)
The main attention is given to the problems of etiological diagnostics of acute tonsillitis in children in Russia and foreign countries, and to the principles of well-grounded antibacterial treatment, presented in modern guidelines, and to the methods of prophylaxis.Key words: children, acute tonsillitis, diagnostics, treatment, prophylaxis.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(2):130-135)